Utilization Of Polypropilene Glycol As Anti Foaming Agent On Evaporation Of Detergent Radioactive Liquid Waste - Zainus Salimin (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Utilization Of Polypropilene Glycol As Anti Foaming Agent On Evaporation Of Detergent Radioactive Liquid Waste. The treatment of radioactive liquid waste in Serpong nuclear facilities is performed by the sequences processes of reduction volume by evaporation and then immobilization of its radionuclides by cementation. The existing evaporator has the treatment capacity of 750 l/h of liquid waste. The nuclear laundry system for cleaning and decontamination of contaminated cloths generates the detergent radioactive liquid waste. The evaporation of detergent liquid waste at the present requires the silicone oil anti foaming agent to prevent the contamination of evaporation distillate caused of carry-over by the foam. For looking the utilization alternative of another anti foaming, the study of utilization of polypropylene glycol as anti foaming agent on the evaporation of detergent liquid radioactive waste has been performed. The evaporation experiment was performed for simulation liquid waste having the Cs-137 activity of 14,8 Bq/ml and dry extract content of 5 g/l by variation of the detergent concentration of 0,1247; 0,1496; 0,187; 0,374; 0,748; and 1,496 g/l. During evaporation, the boiling liquid level be kept by feeding of liquid waste and the generated foam attacks by polypropylene solution injection. Every 15 minutes the sampling of evaporation distillate and concentrate are done for analysis of its Cs-137 activity and extract contents. The result of experiment indicates that on the evaporation of solution containing detergent concentration of 0,1247 to 0,167 g/l gives the effective defoaming process in which the ulitization of polypropylene as antifoaming agent can prevent the contamination of distillate due to the foam can be eliminated properly. On the evaporation of solution on the detergent concentration of 0,374 to 1,496 g/l, the foam can be controlled there is small Cs- 137 contamination of distillate on the value of its clearance level. The evaporation of solution on the detergent concentration of superior than 1,496 g/l, the foam can not be controlled by utilization of antifoaming agent causing the significance value of distillate contamination. By utilization of polypropylene as antifoaming agent, the Cs-137 activity of distillate can be decreased on the value of clearance level. Normally the Cs-137 activity on the concentrate will increase but on its actually result there is decreasing of concentrate activity cause of the Cs-137 sorbtion capability of polypropylene glycol. Every of polypropylene glycol molecule has the functional group of OH on its furthest tip. When the polypropilene glycol molecule contacts with the water molecule so two H+ ions be released from polypropilene glycol forming the ions of – ORO-. The Cs+ on the solution will attached by –ORO- to form CsOROCs so the Cs concentration on the concentrate will decreased.